Temporal binding and social perception – A replication study - David H.V. Vogel; Manuela Woschei; Mathis Jording; Peter H. Weiss; Kai Vogeley (PLoS ONE, 2026)
Previous studies reported action-effect binding for social contexts in a variety of experimental contexts. When confronted with social information, perceptual or conceptual, participants underestimated the duration of time intervals between their actions and subsequent social events, as compared to only observing social events. Current evidence demonstrates stronger temporal binding both for conditions of believing in an interaction with a social partner, and for perceiving an interaction partner. Fewer data exist about the influence of exclusively perceptual social cues such as interaction with a face stimulus. We here report on a study investigating this so-called social hyperbinding for face perception. 40 participants performed a duration estimation task in four blocks involving either the active manipulation of gaze direction, the active manipulation of a geometric pattern, the passive observation of gaze direction, or the passive observation of movement in a geometric pattern. Although results indicated trends towards shorter time estimates for the active manipulation of gaze, with no visible differences in time perception for the other three conditions, our analysis did neither confirm temporal binding nor social hyperbinding for face stimuli. This finding challenges the theory of social hyperbinding for face stimuli. While stronger temporal binding for real and believed interactions with another human has been reliably replicated in the literature, the results from this experiment cannot confirm increased binding for face-like stimuli.